2009
DOI: 10.1002/j.2048-7940.2009.tb00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Perceived Burden for Korean and American Informal Caregivers of Stroke Survivors

Abstract: Little is known about the burden of caring for stroke patients cross-culturally. This article compares the perceived burden for caregivers of stroke survivors in Korea and the United States. A brief interview was conducted to determine specific problem areas for caregivers. Caregiver burden (The Sense of Competence Questionnaire) and social support (The ENRICHD Social Support Inventory) were also measured. Overall sense of burden from caregiving was higher in the Korean cohort than in the Seattle cohort. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
(48 reference statements)
0
14
0
1
Order By: Relevance
“…In contrast, an American study found that increased caregiver burden is more closely correlated with lack of time for self. 858 Smith and colleagues 859 found that the caregiver needs varied as a function of age. Younger caregivers want information and training and are more inclined to criticize the healthcare system, whereas older caregivers need support to maintain a positive outlook and are less inclined to criticize the healthcare system.…”
Section: Social and Family Caregiver Supportmentioning
confidence: 99%
“…In contrast, an American study found that increased caregiver burden is more closely correlated with lack of time for self. 858 Smith and colleagues 859 found that the caregiver needs varied as a function of age. Younger caregivers want information and training and are more inclined to criticize the healthcare system, whereas older caregivers need support to maintain a positive outlook and are less inclined to criticize the healthcare system.…”
Section: Social and Family Caregiver Supportmentioning
confidence: 99%
“…Furthermore, a statistically significant (p≤0.05) correlation between caregivers' ages and perceptions of social support was noticed. In other words, the older the caregiver, the greater his/her perception of social support (27) . In the present study, the variable age only presented a correlation to the material dimension of the social support questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Literature search has revealed some reports from the developed countries, but hardly any from the developing countries. [1]…”
Section: Introductionmentioning
confidence: 99%